The uniform insurance law = قانون التأمين الموحد - Egypt (2025)
Part-1: Insurance and reinsurance and related insurance services professions and activities --Chapter-1:General provisions -- Insurance activity --Provisions of certain types of insurance --insurance pools activity -- Government insurance funds activity -- Private insurance funds activity -- Activity of federation, ancillary bodies -- representation offices -- Insurance professions -- Final provisions -- Part-2: Insurance sector companies, related services and supervision thereof -- Part-3: Settlement of disputes and penalties